Tropical cyclone track prediction by a high resolution limited area model using synthetic observations - PRASAD, K.; RAO, Y.V. RAMA; SEN, SANJIB (MAUSAM, 1997)
ABSTRACT. Results of tropical cyclone track prediction experiments in die Indian seas by a high resolution limited area numerical weather prediction model (1° × 1° lat./long. grid) are presented. As the tropical cyclones form in data sparse regions of tropical oceans, and are, therefore, not well analysed in die initial fields, a scheme has been developed for generation of synthetic observations -based on die empirical structure of tropical cyclones, and their assimilation into the objective analysis, for preparing initial fields for running a forecast model. Experiments on track prediction have beat : conducted for die cyclones forming in the Bay of Bengal and Arabian Sea during the period 1990-95. Forecast errors of the model for 24 hr and 48 hr forecasts have been computed. A sensitivity experiment has been carried out to demonstrate the importance of initial humidity field on forecast model performance. The experiment brings out crucial important of the initial humidity field prescription in accurate track prediction by die forecast model.